Green Investment Model for Smallholder Oil Palm Plantation in Bengkalis Riau - MASHURI, Mashuri; ZULKARNAIN, Zulkarnain; ZULFADIL, Zulfadil; SUWONDO, Suwondo (Journal of Environmental Management and Tourism; Vol 12 No 7 (2021): JEMT Volume XII, Issue 7(55), Winter 2021DO - 10.14505//jemt.v12.7(55).03, 2021)
The level of smallholder oil palm productivity in the Bengkalis Regency is still low. From 2014 to 2018, the productivity level was between 1.3 tons/ha to 2.8 tons/ha. This study aims to design an investment model to enable farmers to obtain maximum and sustainable production results. The analysis used in this study was a prospective analysis. The results showed that there were eight factors identified that caused smallholder oil palm production to be unsatisfactory, such as the price of fresh fruit bunches, land fertility, use of fertilizers, labor, farmer education, farmer group interaction, conservation techniques, and use of superior seeds. The interaction between factors is an investment model that farmers need to consider before investing.